Peran Mahasiswa KKN Kelompok 172 UINSU dalam Pemberantasan Buta Huruf di Kalangan Masyarakat (Studi Kasus Desa Binabo Julu, Kec. Barumun Baru, Kab. Padang Lawas) - Sahdin Hasibuan; Maya Dian Eka Sari; Siti Hamizah Harahap; Mei Sahriani Rambe; Serly Marpaung; Hamdi Maulana Hasibuan (MODELING: Jurnal Program Studi PGMI, 2023)
Illiteracy is one of the conflicts experienced by some countries, according to information from the Ministry of Education and Culture (Kemendikbud, 2021) it is explained that the percentage of illiteracy in Indonesia in 2019 is 1.78% or approximately 3,081,136 people, and in 2020 reduced by about 1.71%, or about 2,961,060 people. Eradication of illiteracy in the Qur'an needs to be done from a young age, because children are the future generation. Children who can read the Qur'an can find out the content of the Qur'an will not have a bad influence on themselves and others. Al-Qur'an is not only a human input/advice when taking photos of it, but reading the Qur'an is also one of the motives for children's reading literacy. This study applies a literature learning approach to answer the research objectives. Literature created by combining the study of journal articles on themes that are in accordance with the objectives of the research, namely the Role of Students of Community Service 172 Uinsu in Eradicating Illiteracy (Case Study in Binabo Julu Village, Barumun Baru District, Padang Lawas District. Illiteracy also has the inability of the population in reading and writing. Illiterate humans will find it too difficult to imitate the improvements around them, therefore this illiteracy must be eliminated quickly to improve the lives of the population. In this case, the students of KKN group 172 want to develop their reading, writing, arithmetic and functional skills which develop the initial human capacity of a limited population. Binabo Julu Village Barumun Baru District, Padang Lawas Regency is able to develop active development and implementation of national formation. The results of this eradication are accepted using a program that has proven to be good or comparable to the first goal in the program was created Those are the children of Binabo Julu Village, Kec. Barumun Baru, Kab. Padang Lawas can read, count, and write. The solution given by the 172 Uinsu KKN students in eradicating Al-Qur'an illiteracy in Binabo Julu Village is the first in the family environment. Second, in the school environment, third, increasing preparation time for learning to read the Qur'an, fourth, improving the terms and conditions for learning to read and write the Qur'an, and fifth. Eradication of Al-Qur'an Illiteracy against the Community and Government.